University spin-off firms' internationalization: Importance of skills - Marina Van Geenhuizen; Qing Ye; Manuel Au-Yong-Oliveira (European Regional Science Association (ERSA), 2015)
Technical and industrial competences are increasingly dispersed across the globe, urging young high-technology firms in Europe to increase distances in their knowledge relations. However, establishment and maintenance of such relationships tend to be hampered by many barriers following from short in capabilities, particularly various missing skills in the management team. In this paper, we examine the role of capability factors and particular skills among a specific category of firms, university spin-offs, in building knowledge networks abroad, specially, the spatial reach involved. Such a study is not new for (innovative) SMEs, but it is new for university spin-off firms. We use two samples of university spin-off firms (each about 100 cases) in various European countries in order to identify the importance of capabilities and certain skills in internationalization of knowledge collaboration, and to this purpose we apply various regression models. The sampled firms are of different age and find themselves in different stages of born-global development. We observe that 60 to 70 per cent of the firms employ knowledge relationships abroad, almost 35 per cent of them outside of Europe. The main underlying capability factors are a high education level (PhD), participation in market/business-related training, and a larger firm size. Another factor is a relatively low level of innovation, indicating a support structure from practical application and customer relations in an established market position of the firm abroad. Examples of such support structure are found in civil engineering works and consultancy concerning transportation infrastructure, land use/protection and the oil and gas industry. Furthermore, one set of missing skills in the management team stands out in limiting larger distances in knowledge collaboration, and these are internationalization skills, for example, skills in presentation of the firm and negotiation of important agreements with a partner abroad, dealing with uncertainty in certification issues and patent protection, and skills in branding the product abroad. Most missing skills are of the conceptual and relational type. Due to different stages in born-global development, the differentiation in missing skills is remarkably large, indicating that training to improve skills requires a multi-faceted and customized approach, without a one-size-fits-all solution. The paper concludes with a summary and some ideas for improving training.
Keywords: D03; M13; O32; 330; global knowledge collaboration; capabilities; skills; university spin-off firms